The Stunting Prevention Analysis (From Food Technology Training and Circular Economy Plan) - Indah Epriliati; Julius Runtu; Paini Sri Widyawati (International Journal of Agricultural Social Economics and Rural Development (Ijaserd), 2024)
Stunting is a latent problem, and Indonesia is still struggling to get out of this situation. It falls into the category of chronic stunting due to a lack of balanced nutritional intake. The motto "CeTing MaS BuLe," which means everyone should eat vegetables, fruits, and catfish to prevent the prevalence of stunting, has encouraged people to eat better food in Petiken Village, Gresik, Indonesia. Food diversification is one of the opportunities to encourage children to get a balanced nutritional intake supervised by the Puskesmas, where health cadres spearhead the program. This study was conducted to implement a stunting prevention program with the motto CeTing MaS BuLe through food technology training to improve food diversity skills using catfish, vegetables, and fruits to know the difference in knowledge towards the stunting prevention program with the motto CeTing MaS BuLe and know the sustainable circular economy plan conducted in June-October 2024. The cadres involved consisted of 40 women. Two sets of questionnaires on food science-technology and competency improvement were completed by respondents before and after the training to investigate the variables of knowledge improvement and competency improvement in developing food diversification skills. Data analysis consisted of a two-sample paired t-test and qualitative descriptive adjusted to the indicators of transformative education. The results showed that 80% of the respondents increased their knowledge acquisition scores compared to before the training, and the food diversification skills transformed into very high food products observed in the food competition. However, the paired sample test for competence did not increase significantly after 5 weeks as the earliest evolutionary capacity development. Nutritionally, the product provides 0.98-60.25% protein of the Nutritional Adequacy Rate (RDA) with a production cost of 270-3,333 rupiah/20g. A food production unit called "Dapur Sehat PMT Lokal" has been piloted on a small scale with a 30% rate of return and is considered a potential hub for an economic turnaround plan that can be scaled up over the next 2 years.